Psychological Analysis of Jenang Kutei Judges in Delivering a Verdict of Matai Bilai and Cuci Kampong (Purification Ritual) in Rejang Lebong Regency, Bengkulu Province, Indonesia (Medico Legal Update, 2020)
Jenang Kutai judges or judges of custom law are judges that are selected from traditional leaders, community leaders or religious leaders. They are highly respected as they are considered as a role model and are prestigious in the society. Well-mannered characteristics owned by custom law judges is underpinned by their maturity balanced with applicable norms in the society. As a judge, Jenang Kutai judge should be calm, assertive, fair, and bold in making decision or delivering a verdict. This is done in order to enforce the law. Even though sometimes such judges psychologically have sympathy for the defendant, they have to pass sentence because people they believe that God’s punishment through hazard disaster will come for those who commit the crime and do not enforce the law.